Persuasive systems design features for promoting insurance through E-wallet penetration - Yeh, Jia Yee (2025)
In Malaysia, a significant societal issue persists—the prevalence of a heavily underinsured population, specifically medical and health insurance. The primary contributors to that dissatisfying situation include the demand-supply gap, distribution network gap and security gap. Given these obstacles, insurtech offers an alternative option for the underinsured population to obtain systematic risk protection at a more affordable cost and flexible contract. Nevertheless, the advent of insurtech has not received welcoming responses from the prospects. The persisting issue of the low insurtech penetration rate paves an avenue to study the role of system design within the context of e-wallet mobile applications.